2022
DOI: 10.3390/app12063048
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Class Classifier in Parkinson’s Disease Using an Evolutionary Multi-Objective Optimization Algorithm

Abstract: In this contribution, a novel methodology for multi-class classification in the field of Parkinson’s disease is proposed. The methodology is structured in two phases. In a first phase, the most relevant volumes of interest (VOI) of the brain are selected by means of an evolutionary multi-objective optimization (MOE) algorithm. Each of these VOIs are subjected to volumetric feature extraction using the Three-Dimensional Discrete Wavelet Transform (3D-DWT). When applying 3D-DWT, a high number of coefficients is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Alzheimer's disease (AD) progress could be classified into the following stages (groups) ( Bi et al, 2018 ), namely pre-clinical/cognitively normal (CN), early mild cognitive impairment (EMCI) ( Edmonds et al, 2019 ), late MCI (LMCI), and AD stage. In contrast, Parkinson's disease (PD) is typically categorized into three developmental stages ( Rojas-Valenzuela et al, 2022 ), including cognitively normal, prodromal phase of PD ( Roos et al, 2022 ), and PD. While previous studies ( Junqué et al, 2005 , Leung et al, 2010 ) have reported reductions in hippocampal volume among patients with AD and PD, there has been limited attention given to other morphological changes.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) progress could be classified into the following stages (groups) ( Bi et al, 2018 ), namely pre-clinical/cognitively normal (CN), early mild cognitive impairment (EMCI) ( Edmonds et al, 2019 ), late MCI (LMCI), and AD stage. In contrast, Parkinson's disease (PD) is typically categorized into three developmental stages ( Rojas-Valenzuela et al, 2022 ), including cognitively normal, prodromal phase of PD ( Roos et al, 2022 ), and PD. While previous studies ( Junqué et al, 2005 , Leung et al, 2010 ) have reported reductions in hippocampal volume among patients with AD and PD, there has been limited attention given to other morphological changes.…”
Section: Introductionmentioning
confidence: 99%
“…This approach seeks to optimize multiple objectives concurrently by considering the interdependencies between them and the associated trade-offs. The Pareto front is a prevalent mechanism in the field of healthcare, particularly in the context of cardiovascular disease, which serves as a means of visualizing the trade-offs involved in decision-making and pinpointing the most desirable solutions [9][10][11]. As an illustration, a metaheuristic multiobjective optimization approach is utilized in a study to identify Alzheimer's disease through the use of multimodal data [9].…”
Section: Introductionmentioning
confidence: 99%